Top of the REAC tube corrosion induced by under deposit corrosion of ammonium chloride and erosion corrosion. (November 2015) - Zhu, Min; Ou, Guofu; Jin, Haozhe; Wang, Kuanxin; Zheng, Zhijian
Abstract: The crystal and deposition behavior of ammonium chloride salt (NH4 Cl) and multiphase flow simulation were investigated by using Aspen software and CFD technology. And the corrosion failure causes of inlet tube explosion of a refinery hydrocracking reactor effluent air cooler (REAC) were studied. The top of 10# carbon steel base tube corrosion is severe, and reveals an inhomogeneous thinning. The field with localized corrosion is mainly distributed in a range of approximately 1.5 m away from the liner tube. The NH4 Cl crystal temperature increases with the increase of feedstock chloride content, and the decrease of injected water volume. The NH4 Cl salt granules mainly distribute in the forepart of an inlet tube of the REAC system. The liquid phase mainly exists in the bottom of an inlet tube, and the gas phase in the top of the tube. Without the enough liquid water, the NH4 Cl in the gas phase crystallizes and deposits on the top of a pipeline, resulting in under deposit corrosion, which interacts with the flow erosive action accelerates the localized corrosion thinning at the top of forepart of an inlet tube. Outside of the range of corrosion failure, the possibility of ammonium salt crystal decreases with decreasing temperature, and the condensed water increases gradually, then the deposited ammonium salts completely dissolve, and reduces the corrosion of downstream system. Highlights: NH4 Cl salt granules mainly distribute in the forepart of an inlet tube of the REAC system. The localized corrosion thinning is localized at the top of forepart of an inlet tube. The failure is caused by under deposit corrosion and erosion corrosion.